METODE APLIKASI BORON UNTUK MENINGKATKAN PRODUKSI TANAMAN JAGUNG (Zea mays L.) HIBRIDA - Suraedah Alimuddin; Andi Ralle; Saida Saida; Netty Syam (Percetakan Umi Toaha Makassar, 2023)
Boron (B) is a micronutrient that has an important role in increasing corn production. Application method B can have different effects on B uptake and crop yield. This study aims to analyze application method B which is more effective in increasing the growth and production of maize plants and to analyze the response of growth and production of Nasa-29, Bisi-2, and Bima-19 URI hybrid maize to application method B. The research was carried out in the experimental garden of Balitserial Bajeng. Gowa Regency. The study was designed using a split-plot design (RPT) with three replications. The main plots were varieties, namely Nasa-29, Bisi-2, and Bima-19 URI, while the subplots were application B through the soil and spraying through leaves. The results showed that the application of B through the soil and the leaves did not show a significant difference in all observed parameters, but the application of B through the soil showed better results. The Nasa-29 variety produced significantly better cob length and cob diameter when given B through the soil, while the Bisi-2 and Bima-19 URI varieties gave no different responses to the B application method for all parameters observed. The application method of B through the soil or the leaves on the three varieties tested did not show a significant difference in yield so the two methods could be an alternative for maize with similar soil conditions in Bajeng, Gowa Regency, and application during the dry season